Cross-National Examination of the Relationship Between Gender Equality and Female Homicide and Rape Victimization - Chon, Donsoo (Violence against women, 2021)
This study is the first cross-national work to examine the impact of gender equality on both female homicide and rape victimization. The data set from the United Nations Office on Drugs and Crime (UNODC) was analyzed for 70 countries. Several gender equality measures were significantly and positively related to rape victimization, but were mostly not significant to female homicide. Findings for rape victimization were consistent with the backlash hypothesis, but such findings may be related to the limitations of police rape rates, such as different legal definitions and police-reporting behaviors across countries.